Influence of seasonal variability on the trophic structure of pelagic communities - Iglesias, Beñat; Louzao, Maite; Bachiller, Eneko; López-López, Lucía; Santos, María; Boyra, Guillermo; Andonegi, Eider; Cotano, Unai; Preciado, Izaskun (Frontiers in Marine Science, 2023)
Seasonal variations in hydrodynamic conditions play a critical role in prey availability at the base of the food web and thus have implications for trophic interactions at higher trophic levels. Here we use the combination of stomach content analysis (SCA) and stable isotope analysis (SIA) to investigate predator-prey interactions and trophic structure of the pelagic fish community of the Bay of Biscay (BoB) in spring and late summer of 2020 and 2021. We found that trophic guilds were more influenced by intra-specific affinities rather than seasonal variability. Main prey for the pelagic fish comprised a set of species belonging to different trophic positions (TPs), from low TP class Thaliacea (salps) to mid TP Engraulis encrasicolus. Vertically migrating meso- and macrozooplankton (mainly copepods and krill) also played an important role as food source for the pelagic fish community showing high trophic overlap among most of species. No differences were detected between the trophic structure in spring and late summer with fish, squids and chaetognaths at the top TPs, whereas krill, meso-zooplankton and salps had the lowest values. However, the TPs estimated using both SCA and SIA approaches were consistently lower in spring, likely due to higher densities and, thus, low TP prey availability in spring. When analyzing ontogenic changes in TPs with predator’s size, significant and positive relationships were found when TP was estimated using SIA but not when using SCA. Overall, our results reveal new insights into the seasonal trophic dynamics of the pelagic fish community of the BoB.